Pengaruh dari Implementasi Kebijakan Keuangan Hijau (Green Banking) Terhadap Kinerja Keuangan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2019-2022 - Siddiq, Aminullah; Sibarani, Hisyam; Wisudanto, Wisudanto (Jurnal Ilmiah Wahana Pendidikan, 2024)
Open mindfulness of the criticalness of natural issues has empowered all segments to require different steps to overcome climate alter. The in general point of this inquire about is to discover out whether the execution of green money related arrangement (green keeping money) has an impact on the monetary execution of banks, particularly those included in KBMI4. In this inquire about, variable X is green managing an account hones which are measured utilizing substance analysis and one of the most monetary execution markers is productivity which can be measured utilizing return on resources (ROA). The comes about of this inquire about appear that green banking practices as measured by the GDBI marker don't have a critical impact on the budgetary execution of keeping money companies, to be specific benefit as measured by ROA amid the 2019-2022 period.